Carbon and pH Modulate the Expression of the Fungal Glucose Repressor Encoding Genes - Vautard-Mey, Géraldine; Fèvre, Michel (Current microbiology, 2003)
The phytopathogenic necrotrophic fungus Sclerotinia sclerotiorum secretes large amounts of oxalic acid and cell wall-degrading enzymes (CWDE). Enzyme synthesis is pH dependent and subject to carbon catabolite repression. Because of the possible involvement of the glucose repressor CRE1 in the transcriptional control of the CWDE encoding genes, we studied crel expression with respect to the nature of the extracellular carbon source and the value of the external pH. Comparative analysis of the cre1 homologous gene creA from Aspergillus nidulans was performed with pH-deregulated mutants. The data obtained showed that ambient pH controls the expression level of the carbon repressor genes, and this control does not depend on the pH transcription factor PacC.